Coronary‐Subclavian Steal Syndrome in a Hemodialysis Patient, a Case Report and Review of Literature. Issue 5 (4th March 2013) - Tan, Chieh Suai; Fintelmann, Florian; Joe, Jennifer; Ganguli, Suvranu; Wu, Steven
Abstract Dialysis vascular access associated coronary‐subclavian steal or hypoperfusion syndrome is an uncommon but potentially life threatening condition. Awareness of this syndrome is important in the management of vascular access in hemodialysis patients. We report a case of dialysis vascular access associated coronary‐subclavian steal syndrome and review the literature on its pathogenesis and therapeutic implications.